Accelerated, first‐pass cardiac perfusion pulse sequence with radial k‐space sampling, compressed sensing, and k‐space weighted image contrast reconstruction tailored for visual analysis and quantification of myocardial blood flow. Issue 4 (12th November 2018) - Naresh, Nivedita K.; Haji‐Valizadeh, Hassan; Aouad, Pascale J.; Barrett, Matthew J.; Chow, Kelvin; Ragin, Ann B.; Collins, Jeremy D.; Carr, James C.; Lee, Daniel C.; Kim, Daniel
Abstract : Purpose: To develop an accelerated cardiac perfusion pulse sequence and test whether it is capable of increasing spatial coverage, generating high‐quality images, and enabling quantification of myocardial blood flow (MBF). Methods: We implemented an accelerated first‐pass cardiac perfusion pulse sequence by combining radial k‐space sampling, compressed sensing (CS), and k‐space weighted image contrast (KWIC) filtering. The proposed and clinical standard pulse sequences were evaluated in a randomized order in 13 patients at rest. For visual analysis, 3 readers graded the conspicuity of wall enhancement, artifact, and noise level on a 5‐point Likert scale (overall score index = sum of 3 individual scores). Resting MBF was calculated using a Fermi function model with and without KWIC filtering. Mean visual scores and MBF values were compared between sequences using appropriate statistical tests. Results: The proposed pulse sequence produced greater spatial coverage (6–8 slices) with higher spatial resolution (1.6 × 1.6 × 8 mm 3 ) and shorter readout duration (78 ms) compared to clinical standard (3–4 slices, 3 × 3 × 8 mm 3, 128 ms, respectively). The overall image score index between accelerated (11.1 ± 1.3) and clinical standard (11.2 ± 1.3) was not significantly different ( P = 0.64). Mean resting MBF values with KWIC filtering (0.9–1.2 mL/g/min across different slices) were significantly lower ( P < 0.0001) than those without KWIC filtering (3.1–4.3 mL/g/min) and agreed better with values reported in literature. Conclusion: An accelerated, first‐pass cardiac perfusion pulse sequence with radial k‐space sampling, CS, and KWIC filtering is capable of increasing spatial coverage, generating high‐quality images, and enabling quantification of MBF.